THE EFFECT OF SERVICE QUALITY AND INNOVATION ON TAXPAYER SATISFACTION AND LOYALTY AT THE LUBUK PAKAM PRIMARY TAX SERVICE OFFICE - Rahmat; Slamet Widodo; Elfitra Desy Surya (RADJA PUBLIKA, 2026)
Tax revenue is the main source of state revenue, which plays an important role in financing national development. One of the determining factors for optimizing tax revenue is the level of taxpayer compliance and loyalty. This study aims to analyze the effect of service quality and taxation innovation on taxpayer satisfaction and loyalty at the Lubuk Pakam Tax Office. The research method used is a quantitative approach with a sampling technique using the Slovin formula, resulting in 93 respondents from a total population of 1,265 taxpayers. Data processing was performed using Partial Least Square (PLS) with SmartPLS software. The results showed that service quality had a positive and significant effect on taxpayer satisfaction and loyalty, while innovation had a positive and significant effect on satisfaction but did not have a significant direct effect on loyalty. Taxpayer satisfaction was found to have a positive and significant effect on loyalty and to act as an intervening variable in the relationship between service quality and innovation on taxpayer loyalty. The R² values of 0.684 for satisfaction and 0.886 for loyalty indicate that the model has strong explanatory power. These findings indicate that improving service quality and developing digital tax service innovations can strengthen taxpayer satisfaction, which ultimately encourages loyalty and voluntary tax compliance. This study recommends improving the competence of tax officials, expanding digital innovations, and conducting periodic evaluations of service standards to strengthen taxpayer trust and loyalty.